Multiple pathogens co-exposure and associated risk factors among cattle reared in a wildlife-livestock interface area in Kenya - Manyenya, Sophina; Nthiwa, Daniel; Lutta, Harrison Osundwa; Muturi, Mathew; Nyamota, Richard; Mwatondo, Athman; Watene, Grace; Akoko, James; Bett, Bernard (Frontiers in Veterinary Science, 2024)
Introduction: Understanding multi-pathogen infections/exposures in livestock is critical to inform prevention and control measures against infectious diseases. We investigated the co-exposure of foot-and-mouth disease virus (FMDV), Brucella spp., Leptospira spp. and Coxiella burnetii in cattle in three zones stratified by land use change and with different wildlife-livestock interactions in Narok county, Kenya. We also assessed potential risk factors associated with the transmission of these pathogens in cattle.We identified five villages purposively, two each for areas with intensive (zone 1) and moderate wildlife-livestock interactions (zone 2) and one for locations with low wildlife-livestock interactions (zone 3). We sampled 1,170 cattle from 390 herds through a cross-sectional study and tested the serum samples for antibodies against the focal pathogens using enzyme-linked immunosorbent assay (ELISA) kits. A questionnaire was administered to gather epidemiological data on the putative risk factors associated with cattle's exposure to the investigated pathogens.Data were analyzed using the Bayesian hierarchical models with herd number as a random effect to adjust for the within-herd clustering of the various co-exposures among cattle.Results: Overall, 88.0% (95% CI: 85.0-90.5) of the cattle tested positive for at least one of the targeted pathogens, while 41.7% (95% CI: 37.7-45.8) were seropositive to at least two pathogens.FMDV and Brucella spp. had the highest co-exposure at 33.7% (95% CI: 30.9-36.5), followed by FMDV and Leptospira spp. (21.8%, 95% CI: 19.5-24.4), Leptospira spp. and Brucella spp. (8.8%, 95% CI: 7.2-10.6), FMDV and C. burnetii (1.5%, 95% CI: 0.7-2.8), Brucella spp. and C. burnetii (1.0%, 95% CI: 0.3-2.2), and lowest for Leptospira spp. and C. burnetii (0.3%, 95% CI: 0.0-1.2).Cattle with FMDV and Brucella spp., and Brucella spp. and Leptospira spp. co-exposures and those simultaneously exposed to FMDV, Brucella spp. and Leptospira spp. were significantly higher in zone 1 than in zones 2 and 3. However, FMDV and Leptospira spp. co-exposure was higher in zones 1 and 2 than zone 3. Discussion/conclusion: We recommend the establishment of a One Health surveillance system in the study area to reduce the morbidity of the targeted zoonotic pathogens in cattle and the risks of transmission to humans.